Live Streaming as a Means of Communication in HR Management: Improving Interaction between Employees and Managers - Pardomuan Pardosi; Eko Budiono; Irawan Irawan; Khairil Anwar (Yayasan Adra Karima Hubbi, 2024)
Background. Effective communication between employees and managers is key to successful HR management. In the midst of technological developments, the use of live streaming has been identified as a new means that can improve interaction in internal company communication. This study aims to explore how live streaming can improve interaction between employees and managers in the context of HR management. Purpose. This study aims to analyze the impact of the use of live streaming on improving communication, employee engagement, and relationships between managers and employees in companies that implement this technology. The study also seeks to identify the benefits and challenges that companies face in implementing live streaming for internal communication. Method. This study uses a quantitative method with an experimental approach. The study sample consisted of employees and managers at several companies that had implemented live streaming in their internal communications. Data were collected through questionnaires and semi-structured interviews, which were then analyzed using descriptive statistics and thematic analysis. Results. The results showed that the use of live streaming significantly increased employee engagement in internal communication and strengthened the relationship between managers and employees. Employees feel more satisfied and connected, while managers report increased transparency and more effective direct interactions. This increased engagement also contributes to teamwork productivity and efficiency. Conclusion. The study concludes that live streaming can be an effective tool to improve communication in HR management, create openness, and strengthen interactions between employees and managers. The use of this technology can improve the communication culture in the company, increase employee engagement, and facilitate faster and more informed decision-making.